2022
DOI: 10.1088/1755-1315/1016/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various types and doses of biochar on hybrid maize growth

Abstract: Climate change also has an impact on agriculture, especially at Mediterranean red-yellow soil which is characterized with low fertility. The application of biochar is an alternative to increase soil fertility, as well as promoting the growth and yield of maize in red-yellow Mediterranean soil. The study aimed it determining the appropriate type and dose of biochar in red-yellow Mediterranean soil to support the growth of hybrid maize. The study used a factorial Randomized Completely Block Design (RCBD) with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
4
5
2
Order By: Relevance
“…This suggests that the combination of biochar level and mycorrhiza improve the plant height thereby increasing the wheat growth. This finding is similar to that reported by Rahayu, Nurmalasari, and Aini (2022). These authors showed that at seven weeks following planting, animal waste biochar application enhanced maize development in terms of plant height, leaf count, stem diameter, and dry weight.…”
Section: Resultssupporting
confidence: 91%
“…This suggests that the combination of biochar level and mycorrhiza improve the plant height thereby increasing the wheat growth. This finding is similar to that reported by Rahayu, Nurmalasari, and Aini (2022). These authors showed that at seven weeks following planting, animal waste biochar application enhanced maize development in terms of plant height, leaf count, stem diameter, and dry weight.…”
Section: Resultssupporting
confidence: 91%
“…This study demonstrated that the quantity and type of biochar used on crop biomass had a reciprocal effect (Figure 2). In contrast to the findings of Rahayu et al (2022), this study showed no significant difference in the 7 WAP dry weight of hybrid maize based on the dose or type of biochar applied. The application of 45 trice husk biochar ha -1 , 30 t coconut shell biochar ha -1 , and 15 t wood biochar ha -1 resulted in dry biomass yields of 6.88 t ha -1 , 6.89 t ha -1 , and 7.16 t ha -1 , respectively, at 8WAP (Figure 1).…”
Section: Plant Biomasscontrasting
confidence: 99%
“…In contrast to the results of Rahayu et al (2022), the type of biochar and the dose of biochar separately had no significant effect on the leaf area of maize plants at 7 WAP. Leaf area, which increases with biochar application, is essential for photosynthesis.…”
Section: Leaf Areacontrasting
confidence: 97%
“…The application of biochar with the appropriate dose in plants will help increase microbial activity in the soil and will have an effect on increasing the availability of organic matter in the soil. Optimal organic content in the soil helps in maintaining growth and development in plants [18], 2022 [19]. Crop growth rate: During 30-40 DAS, significantly higher crop growth rate (29.08 g/m2/day) was recorded with (treatment 9) with application of Azospirillum 10g along with Azotobacter 10g/kg seed and Biochar 40 t/ha, However, (treatment-7), (treatment-8) were found to be statistically at par with the higher.…”
Section: Growth Parametersmentioning
confidence: 99%